THE EFFECT OF FISH MEAL REPLACEMENT WITH EXPIRED POWDER MILK IN RATIONS ON THE PERFORMANCE AND NUTRIENT DIGESTIBILITY OF MALE NATIVE CHICKENS (2-10 WEEKS) - M. E. D, PERTIWI; MASTIKA, I M.; NURIYASA, I M. NURIYASA** (Fakultas Peternakan Universitas Udayana, 2017)
The purpose of this study is to determine the effect of fish meal substitution with expired milk in diets on theproductivity of cockerels at the age of 2-10 weeks. This study was carried out in Puger Village, Jember Regency,East Java. A Completely Randomized Design (CRD) was used with five treatments and five replicates. Totally, therewere 25 experimental units and each unit consists of four cockerels fed without fish meal (R0); 25% diets of fishmeal substitution with expired milk (R1); 50% diets of fish meal substitution with expired milk (R2); 75% diets offish meal substitution with expired milk (R3) and 100% diets of fish meal substitution with expired milk (R4). Dietsand water were given ad libitum. The variables observed were performance and nutrient digestibility. It showedthat cockerels fed 75% diets of fish meal substitution with expired milk (R3) produced higher final body weightand nutrient digestibility (P<0.05) compared to treatment R0, R1, R2 and R4. Treatment R3 produced 75.08%digestibility coefficient of dry ingredient and 72,21% digestibility coefficient of crude protein. It can be concludedthat 75% fish meal substitution with expired milk produced better performance and nutrient digestibility comparedto other treatment.